The effects of methanolic extract of clinacanthus nutans L. (belalai gajah) on atherogenic risk markers in a type 2 diabetic rat model - Azemi, Ahmad Khusairi (2021)
Diabetes mellitus is associated with endothelial dysfunction (ED); causing progressive vascular damage. Clinacanthus nutans has been documented to have antioxidant, hypoglycemic, hypolipidemic and anti-inflammatory properties; properties with the potential to improve endothelial function and prevent atherosclerosis development. Firstly, this study aims to evaluate endothelial function, early vascular structural changes, vascular oxidative stress and inflammation in a model of type 2 diabetes (T2DM) rat induced by high-fat diet (HFD) and low-dose streptozotocin (STZ). Secondly, to determine the effects of C. nutans methanolic leaves extract (CNME) on the above parameters on the same model. First part of study: Male Sprague-Dawley rats were divided into non-diabetic and diabetic groups (n=12 per group). Diabetic groups were fed 4 weeks of HFD before intraperitoneal injection of STZ; and sacrificed at week 15. Fasting blood glucose (FBG) and lipid profile were measured prior to sacrifice. Upon sacrifice, the aorta was isolated; endothelial-dependent and -independent relaxations and contractions were determined using the organ bath. Aortic endothelial nitric oxide synthase (eNOS) expression was assessed via Western blotting. Aortic superoxide dismutase (SOD), malondialdehyde (MDA), tumor necrosis factor-alpha (TNF-a), histopathological changes and aortic intima-media thickness (IMT) were also measured. Second part of study: Male Sprague-Dawley rats were divided into non-diabetic and diabetic groups. After seven week of diabetes induction, rats were divided into five groups (n=12 per group): non-diabetic control (C), non-diabetic treated with 4 weeks of CNME (500 mg/kg/daily)(C+CNME), untreated diabetic rats (DM), diabetic treated with metformin (300 mg/kg/daily)(DM+Met) and diabetic treated with CNME (500 mg/kg/daily)(DM+CNME). Rats were sacrificed after 4 weeks of treatment and experimental parameters similar to part 1 of study were performed. Results; First part: Diabetic rats have higher FBG, total cholesterol (TC), triglycerides (TG), lowdensity lipoprotein cholesterol (LDL-C) and atherogenic index (AI) compared to non-diabetic rats. Endothelium-dependent relaxation was decreased while endothelial-dependent and -independent contractions were increased in diabetic rats. eNOS expression was lower in diabetic rats. IMT, MDA and TNF-a levels were increased while SOD activity lower in diabetic rats. Second part: Both DM+CNME and DM+Met groups reduced FBG levels compared to the DM group. Treatment with CNME and metformin in diabetic rats showed lower TC, TG, LDL-C and AI compared to untreated diabetic rats. Both diabetic-treated with CNME and metformin groups significantly improved the impairment in endothelium-dependent vasorelaxation; this was associated with increased expression of eNOS. Treatment with CNME and metformin also reduced endothelium-dependent and -independent contractions in diabetics. Aortic IMT, MDA and TNF-α levels were reduced while SOD activity was higher in both CMNE and metformin treated diabetic rats. These results demonstrated that the T2DM model induced by HFD and low-dose STZ has ED associated with early vascular structural changes, and increased vascular oxidative stress and inflammation. Treatment with C. nutans extract improved endothelial-dependent vasodilatation, reduced endothelial-dependent and - independent contractions, increased eNOS expression and SOD levels, lower AI, MDA, TNF-a levels, and reduced IMT in aorta of T2DM rats; all these effects were comparable with metformin-treated diabetic rats. Thus, the methanolic extract of C. nutans leaves has the potential to be further explored as an adjunct in the treatment of T2DM to prevent or reduce severity of diabetes induced atherosclerosis.